2007
DOI: 10.1016/j.jcrs.2007.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Phacoviscocanalostomy versus cataract surgery only in patients with coexisting normal-tension glaucoma: Midterm outcomes

Abstract: Phacoviscocanalostomy lowered IOP and maintained postoperative visual outcomes; it was safe and effective in elderly patients with coexisting NTG and cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
(56 reference statements)
1
11
0
1
Order By: Relevance
“…Shoji et al showed that combining cataract surgery and non-penetrating surgery does not have a negative effect on post-operative BCVA in comparison with phacoemulsification by itself [28]. Our study shows, similarly as in the majority of other studies, that after a slight reduction in the initial post-operative period, the BCVA after DS returned to the baseline level after one week and stabilised around the third month [7-9, 14, 28, 29].…”
Section: Discussionsupporting
confidence: 84%
“…Shoji et al showed that combining cataract surgery and non-penetrating surgery does not have a negative effect on post-operative BCVA in comparison with phacoemulsification by itself [28]. Our study shows, similarly as in the majority of other studies, that after a slight reduction in the initial post-operative period, the BCVA after DS returned to the baseline level after one week and stabilised around the third month [7-9, 14, 28, 29].…”
Section: Discussionsupporting
confidence: 84%
“…11,23 As clarifi ed in the current study, considering the differences in the preoperative IOP levels may be a clue to understanding these discrepancies. Hayashi et al 23 reported a mean IOP decrease of 4.6 ± 4.6 mmHg (22.4%) in cases of POAG, which was more than double the IOP reduction of 1.9 mmHg (11.4%) or 1.7 mmHg (9.9%) after cataract surgery alone reported by Shoji et al 11 as well as those in the current study. The baseline IOP level of 20.5 mmHg in the report of Hayashi and others 23 was higher than that of Shoji and others 11 of 16.7 mmHg and that of 17.6 mmHg in the current study.…”
Section: Discussionmentioning
confidence: 71%
“…These 1492 eyes were treated by one of the following procedures: Lectomy-MMC alone, 186; Phaco-Lectomy MMC, 99; Phaco-VCS, 522; VCS alone, 16; Phaco-lotomy, 127; Lotomy alone, 17; and PEA+IOL alone, 525 eyes. Our surgical procedures for lotomy, 7,8 Phaco-lotomy, 8,9 Lectomy-MMC, 10 Phaco-VCS, 9,11 and PEA+IOL 11 have been reported previously.…”
Section: Methodsmentioning
confidence: 87%
“…The report was confounded by the free use of glaucoma medications postoperatively – and in this case by a protocol requirement to keep the postoperative IOP ≤ 21 mmHg with medication – but the control arm of cataract surgery alone showed a decrease of 1.0 ± 3.3 mmHg from baseline medicated IOP, and with a small reduction in mean requirement for glaucoma medication postoperatively (1.4 vs. 1.0). In a normal Normal Tension Glaucoma population, a retrospective study reported IOP lowering of phacoviscocanalostomy and cataract surgery compared to cataract surgery alone: the decrease in IOP in the cataract‐only group was significant only for the first 6 months; mean IOP decrease at 36 months was 1.0 ± 3.0 mmHg; 9.5% and 2.9% of cases respectively achieved a 20% and 30% decrease in IOP without postoperative glaucoma medication 14 …”
Section: Reviewmentioning
confidence: 99%
“…In a normal Normal Tension Glaucoma population, a retrospective study reported IOP lowering of phacoviscocanalostomy and cataract surgery compared to cataract surgery alone: the decrease in IOP in the cataract-only group was significant only for the first 6 months; mean IOP decrease at 36 months was 1.0 Ϯ 3.0 mmHg; 9.5% and 2.9% of cases respectively achieved a 20% and 30% decrease in IOP without postoperative glaucoma medication. 14 A recent presentation derived from the Ocular Hypertension Treatment Study reported that cataract extraction in non-glaucomatous, untreated ocular hypertensive eyes (33 patients, 51 eyes) produced a decrease in IOP from 23.9 Ϯ 3.7 preoperatively to 19.6 Ϯ 3.6 mmHg postoperatively (P < 0.001). f It could be speculated that these data suggest that there may be an effect of glaucoma medications in modifying the IOP response from cataract extraction, or even that a 'law of diminishing returns' also applies to cataract surgery when utilized as a component of glaucoma management.…”
Section: Ancillary Data From Glaucoma Surgical Studiesmentioning
confidence: 99%